Pengelolaan Beasiswa KIP Kuliah Di Institut Agama Kristen Negeri/IAKN Tarutung - Roni Ulina Sitio; Yayuk Erawati Siahaan; Novita Elisabeth Pakpahan; Tetti Manullang (International Forum of Researchers and Lecturers, 2024)
Education is something that is considered important in everyone's life. Unfortunately, many people are not fortunate enough to receive an education. This is due to poverty. From this, the government finally set regulations through Law No. 12 of 2012 concerning Higher Education which authorizes the government to realize justice, affordability, and equity in obtaining quality higher education related to the benefits of social progress, prosperity, and independence. Therefore, the government finally issued the Indonesia Smart Card (KIP) policy to overcome this problem, because there are still many students who are still in school but drop out because of financial problems. The purpose of this research is to see how the management of the KIP Lecture scholarship at IAKN Tarutung. This research method was conducted with the philosophy of postpositivism, investigating the state of natural objects and using a descriptive qualitative approach with purposive sampling. The KIP college scholarship at IAKN Tarutung provides an opportunity for students who excel but have economic limitations to get higher education in college.